Influence of sub-clinical endometritis on early pregnancy predictors and proinflammatory cytokines in circulating immune cells in dairy cows - Poit, Diego Angelo Schmidt; Ferraz, Priscila Assis; de Andrade Bruni, Gabriela; de Andrade Bruni, Giulia [UNESP]; Nishimura, Thiago Kan; Motta, Igor Garcia; Feltrin, Isabella Rio; Pugliesi, Guilherme (FapUNIFESP (SciELO), 2024)
In Experiment 1, PBMC were isolated from cows considered healthy or with SCE (n=6/group) on Days 0 (estrus) and 7 (diestrus) of a synchronized estrous cycle. In Experiment 2, on D21 (D0 was defined as the day of Fixed Timed Artificial Insemination (FTAI), cows were evaluated by ultrasonography to assess luteal blood perfusion and PBMC were isolated. On D32, cows were classified into: healthy pregnant (n=7), pregnant with SCE (n=4), healthy non-pregnant (n=8), and non-pregnant with SCE (n=10). Gene expression of ISGs (ISG15, OAS1, MX1 and IFI6) and proinflammatory cytokines (IL1-β, TNF-α and IFN-γ) were determined. Expression of ISG15, MX1, IFI6, TNF-α and IFN-γ did not differ between SCE and healthy cows and between Days 0 and 7. Expression of OAS1 and IL1-β were higher (P=0.02) on Day 7 than Day 0, regardlees of the SCE presence. In Exp.2, ISG15 abundance was 2.5-fold greater (P=0.0008), TNF-α was 2.2-fold greater (P=0.05), and IL1-β tended (P=0.06) to be 2.4-fold higher in pregnant than non-pregnant cows. Luteal blood perfusion was greater (P=0.01) in pregnant animals. In conclusion, OAS1 and IL1-β are transcripts upregulated in PBMC at diestrus, regardless of SCE occurrence. Proinflammatory cytokines are not affected by SCE occurrence, but IL1-β and TNF-α are upregulated in pregnant animals on D21 of pregnancy. ISG15 abundance is a good pregnancy predictor, regardless SCE presence.
Keywords: immune response; interferon; pregnancy; Th1 cytokines; uterine disease